The effectiveness of PjBL-STEM learning models in improving High school students' deep learning skills in Artificial Intelligence topics - Prihatin, Relly; Sukmawati, Fatma; Santosa, Eka Budhi; Cahyono, Budi Tri; Juwita, Ratna (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of Project-Based Learning integrated with Science, Technology, Engineering, and Mathematics (PjBL-STEM) models in enhancing high school students’ deep learning skills within the domain of Artificial Intelligence (AI). As AI becomes increasingly ingrained in our society, fostering a deep understanding among students is critical. Traditional teaching methods often emphasize rote memorization, which may not sufficiently develop higher-order thinking skills. Conversely, PjBL-STEM promotes active learning, problem-solving, creativity, and collaboration, which are key attributes of deep learning. This paper explores theoretical foundations, reviews relevant literature, discusses implementation strategies, and analyzes empirical evidence, ultimately demonstrating that PjBL-STEM significantly enhances deep learning in AI topics at the high school level.